De la perception des disfluences normales et sévères à leurs origines articulatoires - Didirkova, Ivana; Štenclová, Ľubomíra; Hirsch, Fabrice (Neophilologica, 2016)
The aim of this work is to verify which acoustic clues allow listeners to differentiate stutteringlike disfluencies (SLD) and other disfluencies (OD). Furthermore, we would like to distinguish OD and SLD on the articulatory level by observing the laryngeal activity. The results show that listeners’classification of a disfluency as stuttering-like or other is based on abnormal prosodic structures and localization of the disfluency.